Implementasi Strategi Percepatan Penghapusan Kemiskinan Ekstrem di Kabupaten Kotawaringin Barat - Wibowo, Indra; Muhammad, Adji Suradji (Universitas Syiah Kuala, 2025)
Presidential Instruction Number 4 of 2022 concerning the Acceleration of the Eradication of Extreme Poverty targets 0 (zero) percent of extreme poverty by 2024. However, until December 2024 there is still data on poor people in West Kotawaringin Regency. Therefore, this study aims to determine how the implementation of the strategy to accelerate the eradication of extreme poverty is carried out by the West Kotawaringin Regency Government, Central Kalimantan Province. This study uses a qualitative descriptive approach using the concept of strategy implementation from J. David Hunger and Thomas L. Wheelen (2023) which is seen from program implementation, budget implementation and procedure implementation. Data sources are in-depth interviews and literature studies, report documents, and data from the Central Statistics Agency. The results of this study indicate that program implementation can be said to have covered the extreme poor, especially programs in the field of social assistance, while capital assistance and business assistance have not been maximized. Second, implementation in terms of the budget still needs to be improved, especially for strategies to increase community income, and third, from the implementation of procedures, there is innovation from the Regional Government through the Regent's Regulation concerning the repair of Uninhabitable Houses (RTLH) and assistance for the construction of new buildings.